2018
DOI: 10.1186/s12935-018-0562-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of CXCL5 expression in cancer patients: a meta-analysis

Abstract: BackgroundCXCL5 is a member of the CXC-type chemokine family, which has been found to play important roles in tumorigenesis and cancer progression. Recent studies have demonstrated that CXCL5 could serve as a potential prognostic biomarker for cancer patients. However, the prognostic value of CXCL5 is still controversial.MethodsWe systematically searched PubMed, Embase and Web of Science to obtain all relevant articles investigating the prognostic significance of CXCL5 expression in cancer patients. Hazards ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 48 publications
3
25
0
Order By: Relevance
“…In postoperative survival analysis of patients after complete pancreatic cancer resection, the mean survival time of CXCL5 expression group is 25.5 months, shorter than the negative groups [31]. CXCL5 overexpression was also reported to be inversely associated with overall survival of patients with intrahepatic cholangiocarcinoma and hepatocellular carcinoma [5].…”
Section: Cxcl5 As a Potential Prognostic Biomarkermentioning
confidence: 96%
See 2 more Smart Citations
“…In postoperative survival analysis of patients after complete pancreatic cancer resection, the mean survival time of CXCL5 expression group is 25.5 months, shorter than the negative groups [31]. CXCL5 overexpression was also reported to be inversely associated with overall survival of patients with intrahepatic cholangiocarcinoma and hepatocellular carcinoma [5].…”
Section: Cxcl5 As a Potential Prognostic Biomarkermentioning
confidence: 96%
“…The results of multiple logistic regression analysis showed that CXCL5 expression level is a significant risk factor for N phase (N2, N3) in gastric cancer but is not associated with T phase [64]. According a recent meta-analysis, CXCL5 expression level in tumor tissues was found to act as an independent prognostic factor for survival in cancer patients [5]. In postoperative survival analysis of patients after complete pancreatic cancer resection, the mean survival time of CXCL5 expression group is 25.5 months, shorter than the negative groups [31].…”
Section: Cxcl5 As a Potential Prognostic Biomarkermentioning
confidence: 99%
See 1 more Smart Citation
“…CXCL5 is a proangiogenic chemokine and a strong attractant for granulocytes and is secreted by various immune-and specific non-immune cells. In the context of cancer, CXCL5 has also been associated with late-stage disease and promotion of metastases [55][56][57]. Since the CXCL5 gene is not among the LATE genes, caution is advised regarding cause and effect of high CXCL5 plasma levels in subjects with LOY.…”
Section: Loy In Blood Is Associated With Changes In the Plasma Proteomementioning
confidence: 99%
“…It is also involved in cancer proliferation in different tissues [29][30][31]. Its clinical value for cancer prognosis is also recently becoming very significant [32,33].…”
Section: Introductionmentioning
confidence: 99%